Relationship between Diabetes Self-Management and the Use of Health Care Apps: A Cross-Sectional Study - Inagaki, Satoshi; Kato, Kenji; Abe, Kozue; Takahashi, Hiroaki; Matsuda, Tomokazu (ACI Open, 2023)
Background People with diabetes are increasingly using smartphone health care applications (apps) to manage their health. However, few studies have examined the percentage of people with diabetes using health care apps and their relationship to self-care.Objective The purpose of this study is to determine the prevalence of health care apps among people with diabetes and the relationship between app use and self-management.Methods A cross-sectional study was conducted using an online survey among people with type 2 diabetes. Multiple linear regression analysis was conducted using the scores of the Japanese version of Summary of Diabetes Self-Care Activities and exercise and general diet subscales as the objective variables.Results Of 253 participants included in this study, 61 (24.1%) used health care apps. Approximately 20% of those aged ≥ 60 also used health care apps. Use of health care apps was a significant predictor of physical activity frequency along with autonomous motivation (p < 0.001). Participants who used health care apps showed a 0.91 point higher physical activity score than those who did not. Regarding the general diet score, the use of health care apps was not significantly associated with dietary habits (p = 0.29).Conclusion Among people with type 2 diabetes, 24.1% used health care apps, and self-management scores of exercise were significantly higher in people with diabetes who used health care apps than in those who did not.
Keywords: patient self-care; home care and e-health; telemedicine and telehealth; consumer health informatics; diabetes mellitus; chronic disease